Sonoelastography of the Achilles Tendon: Prevalence and Prognostic Value Among Asymptomatic Elite Australian Rules Football Players. Issue 4 (July 2016) - Ooi, Chin-Chin; Schneider, Michal E.; Malliaras, Peter; Jones, Donna; Saunders, Steve; McMahon, Andrew; Connell, David
Abstract : Objective: To investigate the prevalence of sonographic abnormalities at the mid-Achilles tendon among a cohort of asymptomatic professional football players and to determine whether these sonographic abnormalities predict midportion Achilles tendon symptoms. Design: Longitudinal study. Setting: A single competitive season in the Australian Rules Football League. Participants: Forty-two elite Australian Rules football players. Main Outcome Measures: Using ultrasound and sonoelastography, 42 players were examined at baseline and again 9 months later (postseason) for the existence of intratendinous hypoechogenicity, delamination, softening, and neovascularization. The anterio-posterior (AP) thickness and cross-sectional area (CSA) were measured. Players reporting Achilles tendon pain or with Victorian Institute of Sports Assessment-Achilles scores below 80 at the end of the season were classified as symptomatic. Results: At preseason, ultrasound and/or sonoelastographic abnormalities were found in 22 (22/42, 52.4%) asymptomatic players. Baseline AP thickness and CSA were significantly greater in symptomatic players at the end season than those in asymptomatic players (0.57 ± 0.05 cm vs 0.50 ± 0.03 cm; P < 0.001 and 0.67 ± 0.07 cm 2 vs 0.57 ± 0.06 cm 2 ; P < 0.001, respectively). The presence of intratendinous softening and delaminations at baseline was associated with pain onset during the season ( P = 0.046; P = 0.048, respectively). Conclusions: Ultrasound and sonoelastography–detected abnormalities were relatively common among the asymptomatic footballers. Greater AP thickness and CSA and also the presence of intratendinous softening and delaminations were associated with the increased risk of developing symptoms. Clinical Relevance: Conventional ultrasound supplement with sonoelastography may be able to identify elite athletes at risk of Achilles tendon injury, which may, in turn, impact therapeutic decisions.